Integrated drag coefficient formula for estimating the wave attenuation capacity of Rhizophora sp. mangrove forests - Lopez-Arias, Fernando; Maza, Maria; Calleja, Felipe; Govaere, Georges; Lara, Javier L. (Frontiers in Marine Science, 2024)
Recently, bulk drag coefficient (C˜D) formulations used to quantify wave energy dissipation by Rhizophora mangroves were developed from laboratory data; however, these formulations have not yet been validated with field data. Additionally, due to the complex geometry of mangrove trees within forests and spatial variability, common criteria for determining the adequate geometric characteristics of mangrove forests are lacking and are required to obtain accurate definitions for C˜D. This paper addresses these knowledge gaps by proposing a newly integrated C˜D formulation based on the comprehensive characterization of a Rhizophora mangle forest combined with wave measurements in field, and by using numerical modeling for the calibration process. The field campaign consisted of 23 continuous days of recorded wave data and spatial distribution observations of the geometric characteristics of the mangrove forest. The variation in frontal area per unit height per square meter (Ahm) along the mangrove forest was reported for three zones with different densities identified along the study transect, with decreasing root density from the vegetation edge to the forest interior. On average, the incident wave height decreased by 34% at 63 m in mangrove forests, and the wave attenuation ratios (r) varied between 0.001 and 0.01 m-1. To estimate the C˜D values associated with these wave height attenuation ratios, the Simulating Waves Nearshore (SWAN) numerical model was used to calibrate the model results with the field observations. The variation in the tree frontal area along the mangrove forest and the wave conditions at the site are considered during the calibration process. To further characterize C˜D for this type of mangrove species, the C˜D values acquired from the calibration together with the values reported in the literature from laboratory experiments are presented as a function of the Keulegan-Carpenter number (KC). Root diameter is defined as the characteristic length according to the inherent geometric characteristics of a Rhizophora sp. forest. The new formulation allows us to predictably estimate C˜D values that can be used as inputs in drag force-based models to estimate the attenuation of wave energy produced by Rhizophora sp. forests.